ER‐anchored CRTH2 antagonizes collagen biosynthesis and organ fibrosis via binding LARP6. (5th July 2021) - Zuo, Shengkai; Wang, Bei; Liu, Jiao; Kong, Deping; Cui, Hui; Jia, Yaonan; Wang, Chenyao; Xu, Xin; Chen, Guilin; Wang, Yuanyang; Yang, Linlin; Zhang, Kai; et al.
Abstract: Excessive deposition of extracellular matrix, mainly collagen protein, is the hallmark of organ fibrosis. The molecular mechanisms regulating fibrotic protein biosynthesis are unclear. Here, we find that chemoattractant receptor homologous molecule expressed on TH2 cells (CRTH2), a plasma membrane receptor for prostaglandin D2, is trafficked to the endoplasmic reticulum (ER) membrane in fibroblasts in a caveolin‐1‐dependent manner. ER‐anchored CRTH2 binds the collagen mRNA recognition motif of La ribonucleoprotein domain family member 6 (LARP6) and promotes the degradation of collagen mRNA in these cells. In line, CRTH2 deficiency increases collagen biosynthesis in fibroblasts and exacerbates injury‐induced organ fibrosis in mice, which can be rescued by LARP6 depletion. Administration of CRTH2 N‐terminal peptide reduces collagen production by binding to LARP6. Similar to CRTH2, bumetanide binds the LARP6 mRNA recognition motif, suppresses collagen biosynthesis, and alleviates bleomycin‐triggered pulmonary fibrosis in vivo. These findings reveal a novel anti‐fibrotic function of CRTH2 in the ER membrane via the interaction with LARP6, which may represent a therapeutic target for fibrotic diseases. Synopsis: The molecular mechanisms underlying excessive collagen biosynthesis and tissue fibrosis remain unclear. This study reports a role for ER‐localized prostaglandin D2 receptor CRTH2 in promoting collagen degradation and suppressing tissue fibrosis via blocking the ribonucleoprotein LARP6. Caveolin‐1 mediates plasma membrane‐to‐ER trafficking of CRTH2 in fibroblasts. ER‐anchored CRTH2 binds the collagen mRNA recognition motif of LARP6, decreasing collagen biogenesis. CRTH2 depletion enhances injury‐induced lung fibrosis in mice in a LARP6‐dependent manner. A small molecule screen identifies Bumetanide as anti‐fibrotic agent, mimicking CRTH2 binding to LARP6. Abstract : Prostaglandin D2 receptor CRTH2 localizes at the ER and promotes collagen degradation in fibroblasts through competitive binding to mRNA‐stabilizing protein LARP6.